INTERNATIONALISATION OF BENIN ART WORKS - Ananwa, Chika Joseph (Journal of Humanity, 2014)
The artworks of Benin are all about events and achievements, actual or mythical that occurred in the past. These art works was grounded on traditional values and religious beliefs, which also displayed iconographic affinities. Until 15th century A.D, Benin art items were not known outside the ancient Benin kingdom and commanded very little monetary and aesthetic values.The internationalisation of Benin artworks first occurred by accident, because the Europeans that made it possible, were not aware of the art items before coming to the continent. The coming of the Portuguese in 1472 was the first of such event then the Benin artworks were used as exchange for Portuguese goods. The second was the looting of Benin art items, by the British soldiers, in 1897, in what was tagged Benin Punitive Expedition.Other aspects of internationalisation include the display of Benin art items at various museums across the world Benin artworks uploaded in the internet and artefacts on display at various private museums.The aim of this research is to find out why, when and how the Benin artworks became internationalised. This paper also looks at the extent, impact and significances of internationalisation of Benin artworks.